Multilayer body
The laminate structure with a controlled luminescence peak ratio and (meth)acryloyl group-containing coating layer addresses adhesion and barrier issues, providing high adhesion to various inks and effective gas barrier properties.
Patent Information
- Application Number
- JP2024158781
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-13
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-07
AI Technical Summary
Existing laminates face challenges in achieving high adhesion to printed layers made of various inks and maintaining gas barrier properties, particularly with active energy ray-curable inks, due to issues with silicon alkoxide content and molecular weight, leading to voids and reduced adhesion to hydrophilic resins, as well as reduced adhesion to dry inks.
A laminate structure with a specific ratio of luminescence peak intensities, incorporating a coating layer containing a hydrolyzate of a water-soluble resin and metal alkoxide, and a silane coupling agent with (meth)acryloyl groups, laminated on a base film with a metal or inorganic compound layer, ensuring a dense coating and improved adhesion.
The laminate exhibits high adhesion to various inks and maintains excellent gas barrier properties, including water vapor and oxygen barrier, while reducing environmental impact through low solvent use and efficient curing.
Smart Images

Figure 2025000692000007 
Figure 2025000692000001 
Figure 2025000692000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate having excellent adhesion to a printed layer. [Background technology]
[0002] Packaging materials for foods, medicines, daily necessities, etc. are required to have oxygen barrier properties and water vapor barrier properties to prevent deterioration of the contents. Barrier films made of resin films such as polyester and laminated with a metal layer such as aluminum or a metal oxide layer have been used as these barrier packaging materials. In particular, when a metal oxide layer is laminated, the film becomes transparent, providing good visibility, and in packaging food, it is widely used because of its high convenience, such as allowing microwave heating. These films are applied to packaging materials for various purposes by printing characters, pictures, etc. for display purposes, or by laminating them with other resin films.
[0003] Furthermore, in order to prevent deterioration of the gas barrier performance, a protective layer is also laminated on the gas barrier layer, and generally printing is performed on the protective layer.
[0004] Gravure printing, which is the mainstream method for printing on such protective layers, is used because it has excellent printability and adhesion to the protective layer (Patent Document 1). However, gravure printing uses ink that contains a large amount of solvent, which requires a large amount of energy to dry the ink solvent and treat the exhaust, and it also places a large burden on the environment.
[0005] Meanwhile, in recent years, attempts have been made to carry out EB flexographic printing and EB offset printing, in which the ink is cured by irradiation with active energy rays, particularly electron beams (EB), in flexible packaging printing (Patent Document 2). In general, flexible packaging printing is performed by roll-to-roll printing, so the quick drying of the ink is important, and active energy ray curing printing methods have the environmental advantage of containing almost no solvent, as well as the energy saving and high productivity of shortening the drying process without using thermal energy. In addition, curing by electron beam irradiation has excellent transparency and does not require a photopolymerization initiator in the ink, so there is a reduced risk of odor of the printed matter and migration of initiator decomposition components to the contents, and is also excellent in terms of safety in terms of protecting the contents.
[0006] However, active energy ray-curable inks, which are mainly composed of acrylate, have poor adhesion to protective layers. Therefore, a laminate that has excellent adhesion to active energy ray-curable inks by introducing silicon alkoxides having (meth)acrylate groups into the protective layer has been reported (Patent Document 3). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2018 / 3596 [Patent Document 2] WO 2019 / 69736 [Patent Document 3] JP 2022-20129 A Summary of the Invention [Problem to be solved by the invention]
[0008] In the invention described in Patent Document 3, the amount of silicon alkoxide having a (meth)acrylate group introduced is very large, and adhesion to active energy ray curable ink is obtained, but in consideration of other protective layer components such as highly hydrophilic vinyl alcohol resin and silicon alkoxide having a small molecular weight, the introduction of a large amount of highly hydrophobic and large molecular weight (meth)acrylate groups increases the voids in the film and the film cannot be cured densely enough to suppress deterioration of the contents, which is not sufficient to obtain barrier properties, and there is room for improvement. Furthermore, because the amount of silicon alkoxide having a (meth)acrylate group introduced is very large, there is a problem that adhesion to drying inks other than active energy ray curable inks (solvents and water as a medium are thermally dried) is reduced.
[0009] Therefore, an object of the present invention is to provide a laminate that exhibits high adhesion to printed layers made of various inks and also exhibits high gas barrier properties. [Means for solving the problem]
[0010] A preferred embodiment of the present invention is as follows. (1) A laminate in which a metal layer and / or an inorganic compound layer and a coating layer are laminated in this order on at least one surface of a base film, in which the ratio X / Y of the emission intensity X of an emission peak to the emission intensity Y of a reference peak measured under the following measurement conditions from the coating layer side is 5 or more and 300 or less. <Measurement conditions> The coated layer side of the laminate is 1×10 -4 After contacting the laminate with a mol / L solution of 4-Nitro-7-piperazino-2,1,3-benzoxadiazole in THF (tetrahydrofuran) at 60°C for 30 minutes, the laminate was immersed and washed twice in THF, and then cut into a 15mm x 15mm piece. In the emission spectrum measurement, the laminate was excited at 470nm, and the peak intensity of the emission maximum seen at 520 to 550nm was calculated. <Base peak> 1×10 -5A THF solution of mol / L 4-Nitro-7-piperazino-2,1,3-benzoxadiazole was measured in the same manner as for the laminate, using a quartz glass cell with an optical path length of 10 mm. (2) The laminate according to (1), wherein the coating layer contains a hydrolysate of a water-soluble resin and a metal alkoxide and / or a polycondensate thereof. (3) The laminate according to (1) or (2), wherein the thickness of the coating layer is 200 nm or more and 600 nm or less. (4) The laminate according to any one of (1) to (3), wherein the metal layer and / or the inorganic compound layer contains aluminum. (5) The laminate has a water vapor permeability of 1.0 g / m 2 / day or less, and oxygen permeability is 1.0cc / m 2 / day or less. (6) The laminate according to any one of (2) to (5), wherein the coating layer contains 0.25 mol % or more and 1.25 mol % or less of (meth)acryloyl groups based on the total molar amount of metal elements contained in the coating layer. (7) The laminate according to any one of (1) to (6), wherein the ratio X / Y of the emission intensity X of an emission peak to the emission intensity Y of a reference peak measured from the coating layer side of the laminate under the following measurement conditions is 18 or more and 100 or less. <Measurement conditions> The coated layer side of the laminate is 1×10 -4 After contacting the laminate with a THF solution of 1.2 mol / L 4-Nitro-7-piperazino-2,1,3-benzoxadiazole at 60°C for 30 minutes, the laminate was immersed and washed twice in THF and then cut into a 15 mm x 15 mm piece. In the emission spectrum measurement, the laminate was excited at 470 nm and the peak intensity of the emission maximum seen at 520 to 550 nm was calculated. <Base peak> 1×10 -5 A THF solution of mol / L 4-Nitro-7-piperazino-2,1,3-benzoxadiazole was measured in the same manner as for the laminate, using a quartz glass cell with an optical path length of 10 mm. (8) The laminate according to any one of (1) to (7), wherein the base film is a polyolefin-based resin film. (9) The laminate according to any one of (1) to (8), wherein the ratio P1 / P2 of the following peak intensities P1 and P2 detected by measuring the coating layer by an FT-IR-ATR method (attenuated total reflection Fourier transform infrared spectroscopy) is 3.5 or more and 8.0 or less. P1: 1,050~1,080cm -1 Intensity of the largest peak present in P2: 920~970cm -1 Intensity of the largest peak present in (10) The laminate according to any one of (1) to (9), wherein the coating layer contains a metal element M in addition to a water-soluble resin and a hydrolysate of a metal alkoxide and / or a polycondensate thereof, and the ratio m / s of the peak intensity m of a fragment ion derived from the metal element M to the peak intensity s of a fragment ion derived from a segment having a Si-O bond, as measured by a time-of-flight secondary ion mass spectrometer (TOF-SIMS), is 0.05 or more and 10.00 or less. <Measurement conditions> Primary ion species: Bi + (2pA, 50μs) Acceleration voltage: 25 kV Detected ion polarity: positive Measurement range: 100μm×100μm Resolution: 128×128 Etching ion species: O 2+ (2keV, 170nA) Etching area: 300μm×300μm Etching rate: 1sec / cycle (11) The laminate according to any one of (1) to (10), wherein the base film is a film derived from recycling. (12) The laminate according to any one of (1) to (11) above, which is used for packaging material applications. (13) The laminate according to any one of (1) to (12), which is used for printing with an electron beam-curable ink. Effect of the Invention
[0011] According to the present invention, it is possible to provide a laminate that exhibits high adhesion to printed layers made of various inks and also exhibits high gas barrier properties. [Brief description of the drawings]
[0012] [Figure 1] 1 is a schematic cross-sectional view showing a configuration of a laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] A preferred embodiment of the laminate of the present invention will be described in more detail below.
[0014] Base Film The resin constituting the base film according to the present invention is not particularly limited, and examples thereof include polyester resins such as polyethylene terephthalate, polyethylene-2,6-naphthalate, polypropylene terephthalate, and polybutylene terephthalate; polyolefin resins such as polyethylene, polystyrene, polypropylene, polyisobutylene, polybutene, and polymethylpentene; cyclic polyolefin resins, polyamide resins, polyimide resins, polyether resins, polyesteramide resins, polyetherester resins, acrylic resins, polyurethane resins, polycarbonate resins, and polyvinyl chloride resins; and biodegradable resins such as polylactic acid, polycaprolactone, polyglycolic acid, and polyvinyl alcohol. Among these, polyester resins are preferred from the viewpoint of adhesion to the inorganic compound layer and handling, and polyolefin resins are preferred from the viewpoint of ease of recycling. In addition to recyclability, it is preferable that the resin contains 3 to 55% by mass of recycled raw materials relative to the entire resin. The recycled raw materials may be those recycled by mechanical recycling or chemical recycling, and are not particularly limited. Furthermore, the resin constituting the base film may contain a biomass-derived (plant-derived) raw material, and for example, in the case of polyester, it is preferable that either one or both of the raw materials, diol or dicarboxylic acid, contain 10 to 95 mass % of a biomass-derived (plant-derived) raw material based on the entire resin composition. The base film may be unstretched or stretched (monoaxially or biaxially), but is preferably biaxially stretched from the viewpoint of thermal dimensional stability.
[0015] The thickness of the base film is preferably 3 μm or more and 100 μm or less, more preferably 5 μm or more and 50 μm or less, and even more preferably 8 μm or more and 30 μm or less. By making the thickness of the base film 3 μm or more, the rigidity as a support can be maintained, and by making it 100 μm or less, the flexibility as a packaging material is maintained while the conformability is improved, which is preferable. The thickness of the base film is determined by the method described in the examples.
[0016] The polyolefin resin film used for the base film is preferably a film mainly composed of a resin having an olefin hydrocarbon as a main constituent unit. The main constituent unit refers to the monomer unit contained in the resin that has the highest content (unit number), and the main component refers to the monomer unit contained in the resin that has the highest content (mass%) of all the constituent components. Examples of polyolefin resins include ethylene, propylene, 4-methyl-1-pentene, and other α-olefin polymers having alkyl groups on the side chain, and copolymers thereof, or copolymers obtained by copolymerizing α-olefins with acrylic acid, C=C bond-containing carboxylic acid, C=C bond-containing carboxylate, C=C bond-containing carboxylate alkyl ester, and the like, norbornene and cyclodiene polymers, and polymers thereof, which may be single-layered or multi-layered. Among these, it is preferable to include polyethylene or polypropylene because they are relatively inexpensive, and it is more preferable to include polypropylene in terms of heat resistance, and it is even more preferable to use polypropylene as the main component from the same viewpoint. In addition, the film may be unstretched or stretched, but it is preferable to be biaxially stretched from the viewpoint of thermal dimensional stability. The polyolefin resin film preferably has a melting point of 150°C or higher. By setting the melting point to 150°C or higher, heat damage caused by heat during the process of forming a metal oxide layer or processing into a packaging material can be prevented, and the heat resistance after processing is also increased, so that deterioration of the barrier property can be suppressed. The melting point of the film can be measured by DSC (differential scanning calorimetry) using the following method.
[0017] <Measuring method for film melting point> Using a differential scanning calorimeter (EXSTAR DSC6220 manufactured by Seiko Instruments Inc.), 3 mg of a sample is heated in a nitrogen atmosphere from 30°C to 260°C at a heating rate of 20°C / min, then held at 260°C for 5 minutes, and cooled to 30°C at 20°C / min. After being held at 30°C for 5 minutes, the sample is heated again from 30°C to 260°C at 20°C / min, and the peak temperature of the endothermic curve obtained during this heating again is taken as the melting point of the resin composition. When multiple peak temperatures are observed, the highest temperature is taken as the melting point of the resin composition.
[0018] The glass transition temperature (Tg) of the polyolefin resin film is preferably not higher than 50° C. In this embodiment, the flexibility of the film is high even at low temperatures, and the film does not harden even at low temperatures when used as a package, enabling stable use over a wide temperature range.
[0019] In addition, the polyolefin resin film preferably has a smooth surface. The surface smoothness can be expressed by the arithmetic mean height Sa defined in ISO25178 (2012), and Sa is preferably 50 nm or less, more preferably 30 nm or less. Sa can be measured using a non-contact surface observation device, for example, a scanning white light interference microscope manufactured by Hitachi High-Tech Science Corporation. In the present invention, Sa is determined by the method described in the Examples. By smoothing the surface, defects in the inorganic oxide layer laminated on the surface can be reduced, a good inorganic oxide layer can be obtained, and the barrier properties can be improved.
[0020] Metallic and / or inorganic compound layers The laminate of the present invention preferably has a metal layer and / or an inorganic compound layer on at least one surface of the substrate film.
[0021] The metal layer and / or the inorganic compound layer preferably contains one or more elements selected from Groups 2 to 14 (excluding carbon) of the periodic table, and the inorganic compound layer further contains at least one of oxygen and nitrogen. Among these, from the viewpoint of processing cost and gas barrier properties, the metal layer preferably contains aluminum, and more preferably contains aluminum as the main component. The main component refers to the component that has the largest content (mass%) among the components. From the same viewpoint, the inorganic compound layer preferably contains at least one or more elements selected from aluminum, magnesium, titanium, tin, indium, and silicon, and more preferably contains silicon or aluminum. Examples of preferable inorganic compound layers include silicon oxide, silicon oxynitride, and aluminum oxide, and aluminum oxide is particularly preferable. Furthermore, in the inorganic oxide layer, the ratio of aluminum to the total of elements from Groups 2 to 14 (excluding carbon) of the periodic table is preferably 50 atomic % or more.
[0022] When a metal layer is provided, the thickness of the metal layer is preferably 5 nm to 500 nm, more preferably 10 nm to 100 nm. By making the thickness 5 nm or more, the barrier property can be improved, and by making the thickness 500 nm or less, the substrate can be prevented from being damaged by heat during film formation, which is preferable.
[0023] When an inorganic compound layer is provided, the thickness of the inorganic compound layer is preferably 2 nm to 50 nm, more preferably 2 nm to 20 nm, and even more preferably 4 nm to 10 nm. By making the thickness 2 nm or more, defects such as pinholes in the inorganic compound layer can be reduced, and by making the thickness 50 nm or less, cracks can be suppressed, which is preferable.
[0024] The thickness of the metal layer and the inorganic compound layer is determined by the method described in the examples.
[0025] The laminate of the present invention is preferably a laminate in which a metal layer and / or an inorganic compound layer, and a coating layer are laminated in this order on at least one surface of a base film. This embodiment includes a laminate in which a base film, a metal layer, and a coating layer are laminated in this order, a laminate in which a base film, an inorganic compound layer, and a coating layer are laminated in this order, a laminate in which a base film, a metal layer, an inorganic compound layer, and a coating layer are laminated in this order, a laminate in which a base film, an inorganic compound layer, a metal layer, and a coating layer are laminated in this order, and a laminate in which a base film, an inorganic compound layer, a metal layer, and a coating layer are laminated in this order.
[0026] Covering layer The coating layer in the present invention refers to at least one outermost layer of the laminate, and is preferably a layer containing a water-soluble resin and a hydrolysate of a metal alkoxide and / or a polycondensate thereof.
[0027] The laminate of the present invention is preferably a laminate in which a metal layer and / or an inorganic compound layer and a coating layer are laminated in this order on at least one surface of a base film, the coating layer is preferably a layer containing a water-soluble resin and a hydrolysate of a metal alkoxide and / or a polycondensate thereof, and the outermost layer is preferably the coating layer.
[0028] A water-soluble resin is one in which the resin is dispersed in water to a concentration of 5% by mass, heated and stirred at 90°C for 1 hour, and then cooled to room temperature. When 30 mL of the liquid is passed through a type 1 filter paper (compliant with JIS P 3801 (1995)), no residue remains on the filter paper.
[0029] The water-soluble resin of the coating layer preferably contains one or more types of segments selected from a segment derived from a vinyl alcohol resin, a segment derived from a polysaccharide, and a segment derived from an acrylic polyol resin.
[0030] Resins containing a segment derived from a vinyl alcohol resin, a segment derived from a polysaccharide, and a segment derived from an acrylic polyol resin are preferably vinyl alcohol resins, polysaccharides such as methyl cellulose, and acrylic polyol resins, respectively, and vinyl alcohol resins are preferred from the viewpoint of further improving oxygen barrier properties. Examples of vinyl alcohol resins include polyvinyl alcohol, ethylene-vinyl alcohol copolymers, modified polyvinyl alcohol, and the like, and these resins may be used alone or in a mixture of two or more kinds. The average molecular weight of the vinyl alcohol resin (based on JIS K 6726 (1994)) is preferably 500 or more and 3,000 or less. If the molecular weight is smaller than this, the polymer is difficult to fix in the layer, and the barrier properties may be reduced.
[0031] Vinyl alcohol resins are generally obtained by saponifying polyvinyl acetate, and may be partially saponified by saponifying a portion of the acetate groups, or may be completely saponified, but a higher degree of saponification is preferable. The degree of saponification (based on JIS K 6727 (1994)) is preferably 90% or more, more preferably 95% or more. A higher degree of saponification is preferable because it reduces the number of acetate groups with large steric hindrance, reduces the free volume of the coating layer, and increases the crystallinity of the resin, which is advantageous for improving the barrier properties.
[0032] The modified polyvinyl alcohol resin refers to a resin obtained by chemically reacting polyvinyl alcohol with a monomer having a different chemical structure, or by copolymerizing monomers having a different chemical structure. Examples of modified polyvinyl alcohol resins include vinyl ester resins such as vinyl acetate and vinyl propionate, carboxylic acid resins, methacrylic acid ester resins, vinyl ether resins such as methyl vinyl ether, and glycol resins.
[0033] The vinyl alcohol resin-derived segment, the polysaccharide-derived segment, and the acrylic polyol resin-derived segment contained in the coating layer can be analyzed by the following method.
[0034] The film piece is immersed in deuterated isopropanol, and the coating layer composition is dissolved in the solvent, or the coating layer is physically scraped off using a spatula or the like. Whether the coating layer has dissolved or been scraped off can be confirmed by measuring the coating layer thickness in the same manner as in the thickness evaluation method described below. The sample dissolved in the solvent is then subjected to liquid NMR, or the scraped off sample is subjected to solid NMR. 13 By analyzing C and assigning each peak, it is possible to confirm whether each segment is included.
[0035] The metal alkoxide is at least one selected from silicon alkoxides represented by Si(OR)4, hydrolysates of silicon alkoxides, and polycondensates of hydrolysates of silicon alkoxides, which are segments having Si-O bonds, and / or a compound represented by the general formula M(OR) n In the formula, n is a natural number, and M is a metal atom, preferably titanium, aluminum, zirconium, etc. Here, R is an alkyl group, and in particular, a lower alkyl group having 1 to 4 carbon atoms is preferable. In particular, from the viewpoints of reactivity, stability, and cost, for example, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane can be preferably used, and these may be used alone or in a mixture of two or more kinds. These metal alkoxides may be hydrolyzed or polycondensed to form a network.
[0036] The hydrolysis and / or polycondensation of metal alkoxides can be carried out in the presence of water, a catalyst, and an organic solvent. The water used in the reaction is Si(OR)4 and / or M(OR) n The amount of water is preferably 0.8 equivalents or more and 5 equivalents or less relative to the alkoxy group. By making the amount of water 0.8 equivalents or more, it is preferable that the hydrolysis can be sufficiently advanced to form a network. By making the amount of water 5 equivalents or less, it is preferable that the degree of hydrolysis can be adjusted to suppress random network formation, and the free volume of the film can be reduced to improve the barrier property.
[0037] The catalyst used for the reaction of the metal alkoxide is preferably an acid catalyst. Examples of the acid catalyst include, but are not limited to, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, tartaric acid, etc. Usually, the hydrolysis and polycondensation reaction of the metal alkoxide can be carried out with either an acid catalyst or a base catalyst. When an acid catalyst is used, the monomers in the system are easily hydrolyzed on average, and condensation is likely to proceed in a linear or network structure. On the other hand, when a base catalyst is used, the reaction mechanism is such that the hydrolysis and polycondensation reaction of alkoxides bonded to the same molecule is easily promoted, so the reaction product tends to be granular with a large free volume and many voids. Since the voids in the film become a permeation path for water vapor and oxygen, it is preferable to use an acid catalyst. The amount of the catalyst used is preferably 0.1 mol% or more and 0.5 mol% or less with respect to the total molar amount of the metal alkoxide.
[0038] As the organic solvent used in the reaction of the metal alkoxide, alcohols that are miscible with water and the metal alkoxide, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, and n-butyl alcohol, can be used.
[0039] In addition, commercially available silicate oligomers and polysiloxanes can also be used as polycondensates of metal alkoxides. Although silicate oligomers and polysiloxanes can be used alone or mixed with low molecular weight metal alkoxides, it is preferable to use them mixed with low molecular weight metal alkoxides in order to suppress cracks caused by excessive crosslinking. In addition, when using silicate oligomers and polysiloxanes, it is preferable to select those with a linear or network structure, because the free volume of the film is small and the barrier property is easily improved.
[0040] The metal alkoxide contained in the coating layer can be confirmed by analyzing the surface of the coating layer using an FT-IR-ATR method and assigning each peak to confirm whether or not the coating layer contains a segment having an Si—O bond and an MO bond.
[0041] The coating layer in the present invention is preferably obtained by mixing the water-soluble resin with the hydrolysis product and / or polycondensation product of the metal alkoxide, and coating and drying the coating material obtained on the metal layer and / or inorganic compound layer. The ratio of the resin and the hydrolysis product and / or polycondensation product of the metal alkoxide contained in the coating layer is determined based on the mass (SiO2, MO n The mass ratio of the resin / metal alkoxide oxide equivalent mass is preferably in the range of 15 / 85 to 85 / 15, more preferably in the range of 20 / 80 to 65 / 35, even more preferably in the range of 20 / 80 to 50 / 50, and particularly preferably in the range of 20 / 80 to 40 / 60. By setting this ratio at 15 / 85 or more, it is possible to suppress the occurrence of cracks due to the weakening of the film caused by an excess amount of hydrolyzate and / or polycondensate components of the metal alkoxide, which is preferable. By setting it at 85 / 15 or less, it is possible to fix the resin with a network of hydrolyzate and / or polycondensate of the metal alkoxide, which suppresses the deterioration of the water vapor barrier property, which is preferable.
[0042] The coating layer in the present invention is preferably prepared by adding a silane coupling agent having a (meth)acryloyl group to the coating agent obtained by mixing the water-soluble resin and the hydrolysis and / or polycondensation product of the metal alkoxide, which makes it possible to introduce a (meth)acryloyl group into the coating layer. By having a (meth)acryloyl group in the coating layer, when a printing layer is formed on the coating layer using an active energy ray curable ink, the (meth)acryloyl group in the coating layer and the active energy ray curable ink can be crosslinked by radical polymerization, thereby improving the adhesion between the coating layer and the printing layer.
[0043] The (meth)acryloyl group is preferably 0.25 mol% or more, more preferably 0.30 mol% or more, based on the total molar amount of metal elements contained in the coating layer, in order to improve the film adhesion of the active energy ray curable ink. Also, in order to maintain good gas barrier properties, the (meth)acryloyl group is preferably 1.25 mol% or less, more preferably 1.10 mol% or less. This is because the (meth)acryloyl group has a large free volume compared to alkoxides having 4 or less carbon atoms and hydroxyl groups which are hydrolysates thereof, and as the amount of the (meth)acryloyl group added increases, the voids in the coating layer expand, resulting in a decrease in gas barrier properties. Also, as the amount of the (meth)acryloyl group added increases, the number of hydroxyl groups decreases accordingly, so that in the case of dry inks such as urethane, which exhibit adhesion due to intermolecular forces, the film adhesion may decrease.
[0044] The ratio of the emission intensity of the emission peak, X, to the emission intensity of the reference peak, Y, is X / Y. A preferred embodiment of the laminate of the present invention is a laminate in which the ratio X / Y of the emission intensity X of the emission peak to the emission intensity Y of the reference peak measured under the following measurement conditions from the coating layer side is 5 or more and 300 or less.
[0045] <Measurement conditions> The coated layer side of the laminate is 1×10 -4 After contacting the laminate with a THF solution of 1.2 mol / L 4-Nitro-7-piperazino-2,1,3-benzoxadiazole at 60°C for 30 minutes, the laminate was immersed and washed twice in THF and then cut into a 15 mm x 15 mm piece. In the emission spectrum measurement, the laminate was excited at 470 nm and the peak intensity of the emission maximum seen at 520 to 550 nm was calculated.
[0046] <Base peak> 1×10 -5 A THF solution of mol / L 4-Nitro-7-piperazino-2,1,3-benzoxadiazole was measured in the same manner as for the laminate, using a quartz glass cell with an optical path length of 10 mm.
[0047] Since the (meth)acryloyl group is an α-β unsaturated carbonyl compound, it can be converted to a 3-aminopropionate structure by 1,4 conjugate addition of highly nucleophilic primary or secondary amines (Michael addition reaction). By using this reaction to selectively introduce 4-Nitro-7-piperazino-2,1,3-benzoxadiazole, a fluorescent dye having a secondary amino group, into the (meth)acryloyl group, it is possible to quantify the (meth)acryloyl group of the film. Since the fluorescent dye has only one secondary amino group, it reacts with the (meth)acryloyl group at an equivalent ratio of 1:1. In addition, since it is an aliphatic amine with high nucleophilicity, the reaction proceeds even at room temperature without a catalyst. In addition, since it has absorption and fluorescence emission in the visible light region of 400 nm or more, it can be detected spectroscopically. In addition, since the contact time is short, the thickness of the coating layer does not affect the value of X very much. The detailed measurement method is determined by the method described in the examples.
[0048] The presence of a certain amount or more of (meth)acryloyl groups in the coating layer improves adhesion to ink. In the present invention, attention is focused on X / Y as an index of the amount of (meth)acryloyl groups in the coating layer. If X / Y is less than 5, the adhesion between the ink and the film laminate may decrease. From the viewpoint of adhesion, X / Y is more preferably 18 or more. On the other hand, if X / Y exceeds 300, the increase in the amount of (meth)acryloyl groups in the coating layer may enlarge the voids inside the layer, resulting in a decrease in gas barrier properties. In addition, adhesion to dry inks such as urethane, which exhibit adhesion due to intermolecular forces, may decrease. From the viewpoints of gas barrier properties and adhesion, X / Y is more preferably 100 or less.
[0049] The coating layer in the present invention preferably has a thickness of 200 nm or more and 600 nm or less, more preferably 200 nm or more and 500 nm or less. By making the thickness 200 nm or more, the metal layer and / or the inorganic compound layer can be coated without defects and the barrier property can be improved. By making the thickness 600 nm or less, cracks due to thermal shrinkage during curing and insufficient curing can be prevented, which is preferable. The thickness of the coating layer is determined by the method described in the examples.
[0050] In the coating layer of the present invention, the ratio P1 / P2 of the peak intensities P1 and P2 detected by the FT-IR-ATR method is preferably 3.5 or more and 8.0 or less, and more preferably 4.0 or more and 6.5 or less (however, P1: 1,050 to 1,080 cm -1 Intensity of the maximum peak present at 920-970 cm -1It indicates the intensity of the maximum peak present in the. The peak intensity is the absorbance (unitless) at the peak position. ) The FT-IR-ATR method can capture the characteristics of the surface coating layer, where P1 indicates the reaction product Si-O-Si, and P2 indicates the amount of the reaction raw material Si-OH. Therefore, the ratio of peak intensity P1 to P2, P1 / P2, increases as the polycondensation of metal alkoxide proceeds. As the polycondensation reaction of metal alkoxide proceeds, the terminal OH is reduced to form a strong film, improving the barrier properties and improving the moist heat resistance when retorted as a packaging material. When P1 / P2 is 3.5 or more, the terminal OH is reduced to form a strong film, and a layer with excellent barrier properties and moist heat resistance can be obtained. It is preferable to set P1 / P2 to 8.0 or less, as this can suppress cracks and embrittlement due to film shrinkage. P1 and P2 are determined by the method described in the examples. In order to set the ratio P1 / P2 of the peak intensities P1 and P2 detected by the FT-IR-ATR method in a preferred range, it is necessary to sufficiently proceed with the reaction of the metal alkoxide. Since the polycondensation of the metal alkoxide is a dehydration reaction, it can be proceeded by heating. However, since the polyolefin resin film used in the base film constituting the more preferred laminate of the present invention has a lower heat resistance than conventional polyester resins, it is difficult to sufficiently proceed with the reaction. As a result of intensive research, the inventors have succeeded in obtaining a film with suitable properties even in low-temperature processing by mixing a component that can form a network at low temperature. In addition, it has been found that the deterioration of the barrier property in the post-process can be suppressed by adjusting P1 / P2 to 3.5 or more and 8.0 or less.
[0051] When the laminate of the present invention is used as a packaging material, it is heated and pressured during printing and bag making processes. In this case, a coating that forms a moderate network can function as a protective film, which is preferable. On the other hand, for example, if P1 / P2 is less than 3.5, there is a lot of unreacted metal alkoxide, so the coating layer is not cured and is easily scratched, which deteriorates the barrier properties, or the unreacted metal alkoxide cures and shrinks depending on the processing conditions, which deteriorates the barrier properties. On the other hand, if P1 / P2 is more than 8.0, the coating layer becomes brittle, and cracks are easily generated due to the pressure during lamination and the tension during transportation, which may deteriorate the barrier properties.
[0052] The coating layer in the present invention is preferably a layer containing one or more segments selected from a segment derived from a vinyl alcohol resin, a segment derived from a polysaccharide, and a segment derived from an acrylic polyol resin, as well as a segment having a Si-O bond, and in addition, a metal element M.
[0053] The segment derived from a vinyl alcohol resin, the segment derived from a polysaccharide, and the segment derived from an acrylic polyol resin are the water-soluble resins described above, and the segment having a Si-O bond is one or more selected from the group consisting of silicon alkoxides represented by Si(OR)4, hydrolysates of silicon alkoxides, and polycondensates of hydrolysates of silicon alkoxides, among the metal alkoxides described above.
[0054] The metal element M contained in the coating layer excludes silicon Si. The presence of the metal element M in the coating layer makes it possible to make the coating layer dense. It is believed that the reason that the presence of the metal element M in the coating layer makes it possible to make the coating layer dense is that a compound containing the metal element M penetrates moderately into the repetition of Si-O bonds, creating a moderate degree of freedom in the bonds and making it possible to suppress the occurrence of very fine structural defects and cracks compared to repetition of only Si-O bonds.
[0055] The compound containing the metal element M is preferably a complex (chelate) or alcoholate of at least one metal element selected from at least one metal element excluding silicon or a metalloid metal element, and may contain two kinds of metal elements. The metal element M preferably contains a metal element having an empty orbital, and the sum of the element ratios of the metal elements having an empty orbital is preferably 80 atom% or more in the total of 100 atom% of the metal element M (excluding silicon). The metal element M preferably contains at least one metal element selected from aluminum, titanium, and zirconium, and more preferably the sum of the element ratios of aluminum, titanium, and zirconium is 80 atom% or more in the total of 100 atom% of the metal element M (excluding silicon), and further preferably consists of at least one selected from aluminum, titanium, and zirconium, and particularly preferably the sum of the element ratios of titanium and zirconium is 80 atom% or more in the total of 100 atom% of the metal element M (excluding Si), and most preferably consists of zirconium and / or titanium.
[0056] Examples of chelates or alcoholates containing aluminum element include aluminum tris(acetylacetonate), aluminum monoacetylacetonate bis(ethylacetoacetate), aluminum di-n-butoxide monoethylacetoacetate, aluminum di-isopropoxide monomethylacetoacetate, aluminum tris(ethylacetoacetate), and the like.
[0057] Examples of chelates or alcoholates containing titanium element include titanium orthoesters such as tetra-n-butyl titanate, tetraisopropyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, and tetramethyl titanate; and titanium chelates such as titanium acetylacetonate, titanium tetraacetylacetonate, polytitanium acetylacetonate, titanium octylene glycolate, titanium lactate, titanium triethanolaminate, and titanium ethylacetoacetate.
[0058] Examples of the chelate or alcoholate containing zirconium element include zirconium acetate, zirconium normal propylate, zirconium normal butylate, zirconium tetraacetylacetonate, zirconium monoacetylacetonate, zirconium bisacetylacetonate, and the like.
[0059] In order to ensure coating liquid stability when these are added, it is preferable to mix them as a chelate, and examples thereof include aluminum tris(ethylacetoacetate), aluminum monoacetylacetonate bis(ethylacetoacetate), titanium lactate, titanium diethanol aminate, diisopropoxytitanium bis(triethanol aminate), zirconium lactate, etc. Among these, titanium chelates, which can provide stability even with small ligands, are preferred, since reducing the amount of ligand residue after the reaction can suppress an increase in free volume derived from the ligands.
[0060] The polycondensation product of silicon alkoxide that forms the coating layer needs to undergo a sufficient reaction in order to provide a good barrier property, so by mixing a highly reactive metal chelate, it is possible to achieve both appropriate reactivity and stability of the coating solution.
[0061] The coating layer in the present invention preferably has a ratio m / s of the peak intensity m of a fragment ion derived from a metal element M to the peak intensity s of a fragment ion derived from a segment having a Si-O bond, as measured at the center of the coating layer thickness by a time-of-flight secondary ion mass spectrometer (TOF-SIMS), of 0.05 or more and 10.00 or less.
[0062] The ratio m / s of the peak intensity m of a fragment ion derived from a metal element M to the peak intensity s of a fragment ion derived from a segment having a Si-O bond, as measured by a time-of-flight secondary ion mass spectrometer (TOF-SIMS), is determined by the following method.
[0063] <Apparatus and measurement conditions> Time-of-flight secondary ion mass spectrometer TOF-SIMS5 manufactured by ION TOF <Measurement conditions> Primary ion species: Bi + (2pA, 50μs) Accelerating voltage: 25kV Detected ion polarity: positive Measurement range: 100μm×100μm Resolution: 128×128 Etching ion species: O 2+ (2keV, 170nA) Etching area: 300μm×300μm Etching rate: 1sec / cycle.
[0064] <Identifying the center of the coating layer> The thickness of the coating layer is calculated using the thickness calculation method described in the examples, and half of the thickness is set as the central part. Next, the coating layer is analyzed while etching the thickness under the above measurement conditions. The analyzed sample is measured for the crater depth using a stylus-type step gauge (Dektak XTL, manufactured by BRUKER). The measured depth is converted using the average etching rate obtained by dividing the measured depth by the etching time, and the value at the central part is read. If there is no TOF-SIMS measurement data for the part that is exactly half the thickness, the TOF-SIMS measurement data of the measurement point closest to the part that is half the thickness is used. If there is not one measurement point closest to the part that is half the thickness, the average value of m / s calculated from the measurement data of each measurement point is set as the m / s of the part that is half the thickness.
[0065] <Pretreatment conditions> If the coating layer is exposed on the outermost surface, no pretreatment is required, but if other layers are formed on the coating layer, those layers are removed before analyzing the coating layer. The method for removing the layers formed on the coating layer can be various ion etching methods such as argon ion beam etching or chemical treatment to remove the thickness of each layer. The thickness of each layer is determined by the method described in the examples.
[0066] <Analysis method> The raw data is read using the measurement software SURFACE LAB 7.1 for a time-of-flight secondary ion mass spectrometer TOF-SIMS5 manufactured by ION TOF, and peaks assigned to various ions are read from the mass spectrum.
[0067] When m / s is 0.05 or more, a reaction promotion effect can be obtained even under low-temperature processing conditions, and the coating layer can be made dense due to the effect of the metal element M, resulting in a layer with excellent barrier properties and moist heat resistance. m / s is more preferably 0.30 or more, and even more preferably 0.50 or more. When m / s is 0.05 or more, the amount of metal element M present in the coating layer can be made to be a certain amount or more, and the metal element M acts as a catalyst, resulting in a reaction promotion effect even under low-temperature processing conditions.
[0068] It is preferable that the metal element M is one that easily forms a chelate. By forming a chelate, it is possible to ensure reactivity while simultaneously achieving stability in the coating liquid state. Examples of such metal elements include aluminum, titanium, and zirconium. When using a metal chelate containing the metal element M, it is preferable that the metal chelate has an empty coordination site, which is the difference between the valence and the coordination number. In other words, the metal chelate functions as a Lewis acid. The empty coordination site becomes electronically unstable, and since the site is easily attacked, the reactivity is improved, and a reaction promotion effect can be obtained at a lower temperature. In addition, since a metal chelate containing the metal element M can bond multiple silicon alkoxides, it can promote the reaction between adjacent silicon alkoxides. In other words, a highly reactive metal chelate lowers the activation energy of the reaction between silicon alkoxides, and the thermal energy required to promote polycondensation can be reduced, so that a reaction promotion effect can be obtained at a lower temperature.
[0069] Laminate It is more preferable that the laminate of the present invention uses a polyolefin resin film as the substrate so that the packaging material can be recovered and recycled. The polyolefin resin film has a lower glass transition temperature than conventional polyester resins and polyamide resins. Therefore, even while stored in a roll, the film is likely to shrink and become tightly wound due to changes in the surrounding temperature. At that time, the coating layer is strongly pressed against the back surface of the film outside the roll, which causes a problem that the coating layer is more likely to deteriorate than conventional resin substrates.
[0070] As a result of thorough investigation into this issue, it was found that even when tight rolling occurs with polyolefin resin films, barrier degradation can be suppressed by setting the m / s to 0.05 or more and 10.00 or less. Setting the m / s to 0.05 or more provides a reaction promotion effect even under low-temperature processing conditions, making low-temperature processing possible and suppressing stress on the film caused by shrinkage of the coating layer due to additional curing, while setting the m / s to 10.00 or less makes it possible to control the progress of excessive reactions, suppressing embrittlement of the coating layer and suppressing barrier degradation when the film is pressed down by tight rolling.
[0071] Furthermore, after extensive research into this issue, it was found that barrier degradation can be suppressed by setting P1 / P2 to 3.5 or more and 8.0 or less, even when tight rolling occurs with polyolefin resin films. Setting P1 / P2 to 3.5 or more can suppress the application of stress to the film due to shrinkage of the coating layer caused by additional curing, while setting it to 8.0 or less can suppress embrittlement of the coating layer and suppress barrier degradation when the film is pressed down by tight rolling.
[0072] The laminate of the present invention has a water vapor transmission rate of 1.0 g / m 2 / day or less, and 0.5 g / m 2 / day or less. The oxygen permeability is more preferably 1.0cc / m 2 / day or less is preferable, and 0.3cc / m 2The smaller the water vapor permeability and oxygen permeability, the more preferable. There is no particular lower limit, but the water vapor permeability is substantially 0.01 g / m 2 / day, oxygen permeability is 0.01cc / m 2 / day. The water vapor transmission rate is 1.0g / m 2 / day or less, oxygen permeability 1.0cc / m 2 / day or less is preferable because it is possible to prevent deterioration of the contents due to moisture absorption and oxidation when the contents are made into a package. The water vapor transmission rate and oxygen transmission rate are measured by the method described in the Examples.
[0073] The laminate of the present invention can be obtained by forming a metal layer and / or an inorganic compound layer on at least one surface of a substrate film, and then laminating a coating layer on it. The metal layer and / or the inorganic compound layer can be formed by using known methods such as vacuum deposition, sputtering, ion plating, and plasma vapor phase growth, but the deposition method can be used preferably because it can form a film at high speed with good productivity. The deposition method of the vacuum deposition method includes, but is not limited to, electron beam (EB) deposition, resistance heating, and induction heating. In addition, when forming a metal layer and / or an inorganic compound layer on a long resin film roll, it is preferable to cool the main roll for deposition to prevent heat damage of the film, and the temperature is preferably 20°C or less, and more preferably 0°C or less. As a method for obtaining a metal layer, an example can be given of deposition using a target metal as a raw material. As a method for obtaining an inorganic compound layer, in addition to deposition using a compound of a target composition as a raw material, a method can be exemplified in which a metal is used as a raw material and a reactive gas is introduced into the deposited metal vapor to obtain an inorganic compound. For example, when obtaining an aluminum oxide layer, aluminum is used as a deposition material, and a gas containing oxygen is introduced into the evaporated aluminum vapor to form an inorganic oxide layer on the film. The gas introduced may contain a gas having a composition that reacts with the evaporated metal and is incorporated into the layer, and may contain an inert gas or the like to control the film quality. The surface of the resin film on which the metal layer and / or inorganic compound layer is formed may be subjected to a surface modification treatment in order to improve interlayer adhesion. The surface modification treatment may be in-line or off-line, and the modification treatment method is not particularly limited, but examples thereof include known methods such as corona treatment, plasma treatment, ion beam treatment, and flame treatment. These surface modification treatments may be performed using air, as well as argon, nitrogen, oxygen, carbon dioxide, hydrogen, ammonia, hydrocarbons (C n H 2n+2The treatment may be performed under an atmosphere of various gases such as argon, nitrogen, etc., where n is an integer of 1 to 4, or a mixed gas of these. The gas used for the surface modification treatment can be selected depending on the ease of discharge, the energy of the active species obtained, and the type of functional group to be introduced, but it is preferable that the gas contains carbon dioxide gas or oxygen gas for introducing the functional group, and argon or nitrogen gas which easily generates a stable discharge.
[0074] The laminate of the present invention is preferably produced by a production method including a step of applying a coating agent containing a water-soluble resin, a hydrolysate of a metal alkoxide and / or a polycondensate thereof, and a silane coupling agent having a (meth)acryloyl group to the surface of the laminate having a metal layer and / or an inorganic compound layer on at least one surface of a base film, and a drying step. By adopting this embodiment, when a printing layer is formed on the laminate, it is possible to obtain a laminate that exhibits high adhesion regardless of the type of ink and has good barrier properties.
[0075] Another preferred embodiment of the laminate of the present invention is preferably produced by a production method including a step of applying a coating agent containing a water-soluble resin, a hydrolyzate of a metal alkoxide and / or a polycondensate thereof, and a silane coupling agent having a (meth)acryloyl group to the surface of the laminate having a metal layer and / or an inorganic compound layer on at least one side of a polyolefin resin film, and a drying step. Also, it is preferably obtained by a production method of a laminate including a step of applying a coating agent containing one or more selected from silicon alkoxide, a hydrolyzate of silicon alkoxide, and a polycondensate of a hydrolyzate of silicon alkoxide, one or more resins selected from vinyl alcohol resins, polysaccharides, and acrylic polyol resins, a silane coupling agent having a (meth)acryloyl group, and a compound containing a metal element M to the surface of the laminate having a metal layer and / or an inorganic compound layer on at least one side of a polyolefin resin film, and a drying step. By adopting this embodiment, when a printed layer is formed on the laminate, a laminate exhibiting high adhesion and having good barrier properties can be obtained regardless of the type of ink. In addition, a laminate having high water vapor barrier properties and oxygen barrier properties can be obtained while suppressing the environmental load during production. In particular, by adopting this embodiment, the laminate can be sufficiently cured even at low temperatures, and can be sufficiently cured even at high temperatures in a short time, which is preferable because it reduces the environmental load during production. That is, a preferred embodiment of the method for producing a laminate of the present invention is a method for producing a laminate comprising a step of applying a coating agent containing a water-soluble resin, a hydrolyzate of a metal alkoxide and / or a polycondensate thereof, and a silane coupling agent having a (meth)acryloyl group to the surface having the metal layer and / or the inorganic compound layer of a laminate having a metal layer and / or an inorganic compound layer on at least one surface of a base film, and a step of drying.A more preferred embodiment is one in which the base film is a polyolefin-based resin film, and an even more preferred embodiment is one in which the coating agent contains one or more resins selected from silicon alkoxides, hydrolysates of silicon alkoxides, and polycondensates of hydrolysates of silicon alkoxides, one or more resins selected from vinyl alcohol-based resins, polysaccharides, and acrylic polyol resins, a silane coupling agent having a (meth)acryloyl group, and a compound containing a metal element M.
[0076] In addition, from the viewpoint of adhesion and gas barrier properties, it is preferable that the coating agent is obtained by mixing a coating agent 1 containing a water-soluble resin and a hydrolysate and / or polycondensate of a metal alkoxide with a coating agent 2 containing a hydrolysate and / or polycondensate of a silane coupling agent having a (meth)acryloyl group. By adopting this embodiment, it is possible to introduce a particularly large amount of (meth)acryloyl groups onto the surface of the coating layer. In addition, by adopting this embodiment, it is easy to form a laminate in which the coating layer has 0.25 mol % or more and 1.25 mol % or less of (meth)acryloyl groups relative to the total molar amount of metal elements contained in the coating layer, and X / Y is 5 or more and 300 or less.
[0077] The coating method is not particularly limited, and known methods can be used, such as direct gravure, reverse gravure, microgravure, rod coating, bar coating, die coating, and spray coating. The drying temperature after coating is preferably 70°C or more and 150°C or less, and more preferably 90°C or more and 130°C or less. The drying temperature refers to the maximum temperature reached on the film surface. By setting the temperature at 70°C or more, the solvent can be removed to form a layer, and by setting the temperature at 150°C or less, the thermal shrinkage and deformation of the base film can be suppressed. After coating and drying, the laminate of the present invention may be further heat-treated to promote the polycondensation reaction of silicon alkoxide to improve the barrier property. The heat treatment temperature is preferably 30°C or more and 100°C or less, and more preferably 40°C or more and 80°C or less. The heat treatment time is preferably 1 day or more and 14 days or less, and more preferably 3 days or more and 7 days or less. By setting the heat treatment temperature at 30°C or higher, crosslinking of the coating layer can be promoted to improve the barrier properties, and by setting the temperature at 100°C or lower, curling and shrinkage of the film due to heat treatment can be suppressed. Note that the heat treatment temperature refers to the atmospheric temperature.
[0078] The laminate of the present invention is preferably used for packaging material applications. For use as a packaging material, it may be laminated with another resin film for printing or a heat seal layer for bag making, or for improving rigidity. In addition, in order to improve recyclability, the base film, the heat seal layer, and the resin film for improving rigidity are preferably polyolefin resins.
[0079] The laminate of the present invention is preferably used for printing with an electron beam curable ink. By including the laminate in printing with an electron beam curable ink, adhesion with the printed layer is improved and good barrier properties can be obtained, so that deterioration of the contents can be suppressed while the use of the electron beam curable ink reduces the environmental load during the production of the printed layer, which is preferable. EXAMPLES
[0080] The present invention will be described below based on examples. Note that the present invention is not limited to these examples, and these examples can be modified or changed based on the spirit of the present invention, and they are not excluded from the scope of the present invention.
[0081] [Evaluation method] (1) Thickness of the base film The thickness of ten randomly selected points was measured in an atmosphere of 23° C. and 65% RH using an electronic micrometer (K-312A type) manufactured by Anritsu Corp. The arithmetic mean value of the thicknesses obtained at the ten points was regarded as the thickness of the substrate film (unit: μm).
[0082] (2) Arithmetic mean height Sa of the base film Measurements were taken using a scanning white light interference microscope, VertscanVS1540, manufactured by Hitachi High-Tech Science Corporation, a three-dimensional non-contact surface shape measuring device. In the analysis, the attached analysis software was used to remove waviness components from the captured image using polynomial fourth-order approximation surface correction, and then processing was performed using a median (3 x 3) filter, followed by interpolation processing (processing in which pixels for which height data could not be obtained are supplemented with height data calculated from surrounding pixels). The measurement conditions were as follows. Measurement conditions: Objective lens 10x 1x telescope tube Zoom lens 1x Wavelength filter 530nm white Measurement mode: Wave Measurement software: VS-Measure Version 10.0.4.0 Analysis software: VS-Viewer Version 10.0.3.0 ·Measurement area: 0.561×0.561mm 2 .
[0083] (3) Thickness of the metal layer and / or inorganic compound layer The thickness was measured by cross-sectional observation using a transmission electron microscope (TEM). Using a microsampling system FB-2000A manufactured by Hitachi, Ltd., a sample for observation was prepared by the FIB method (specifically, based on the method described in "Polymer Surface Processing Science" (by Akira Iwamori), p. 118-119). Next, the cross-section of the sample for observation was observed using a transmission electron microscope H-9000UHRII manufactured by Hitachi, Ltd., at an acceleration voltage of 300 kV, and the thickness of the metal layer and / or inorganic oxide layer was confirmed at any 10 points. The arithmetic average value of these values was taken as the thickness of the metal layer and / or inorganic oxide layer (unit: nm).
[0084] (4) Thickness of the coating layer The laminate was cut perpendicular to the film surface with a microtome, and the cross section of the laminate was observed and measured with a scanning transmission electron microscope. Observation was performed using a Hitachi Ltd. STEM (scanning transmission electron microscope / H-9000UHRII) and images were taken at three points at a magnification of 100,000 times. The thickness of the coating layer was measured in the three images obtained, and the average value was taken as the thickness of the coating layer (unit: nm).
[0085] (5) The ratio of emission intensity X to the emission intensity Y of the reference peak, X / Y The laminate was cut into 40 mm x 40 mm pieces, and the coated layer side was cut into 1 x 10 -4 The surface was contacted with a THF solution of 4-Nitro-7-piperazino-2,1,3-benzoxadiazole at 60°C for 30 minutes. Next, the laminate was immersed and washed twice in THF, and then the four corners of the washed film piece were cut to 15 mm x 15 mm, and fixed to a quartz plate to prepare a measurement sample. The measurement sample was subjected to fluorescence measurement by a transmission method using a fluorescent phosphorescence spectrophotometer (Horiba, FluoroMax-4P) with 470 nm excitation light, excitation light slit 2 nm, emission slit 2 nm, and a light receiving range of 500 to 700 nm. When a peak of emission intensity was observed at 520 to 550 nm, the peak intensity was calculated as the emission intensity X.
[0086] 1x10 more -5A THF solution of 4-Nitro-7-piperazino-2,1,3-benzoxadiazole (mol / L) was measured using a quartz glass cell with an optical path length of 10 mm. The peak of the emission intensity at 520 to 550 nm obtained by the measurement was calculated as the emission intensity Y of the reference peak, and the ratio X / Y of the emission intensity X to the emission intensity Y of the reference peak was calculated.
[0087] (6) Water vapor permeability According to JIS K 7129 (2008) Method B, measurements were taken at a temperature of 40°C and a humidity of 90% RH using a water vapor transmission rate measuring device ("PERMATRAN (registered trademark)" W3 / 31) manufactured by MOCON / Modern Controls. The measurements were taken twice for two test pieces, and the average of the four measured values was calculated to determine the water vapor transmission rate.
[0088] (7) Oxygen permeability According to the isobaric method of JIS K 7126-2 (2006), the oxygen transmission rate was measured using an oxygen transmission rate measuring device ("OXTRAN (registered trademark)" 2 / 20) manufactured by MOCON / Modern Controls under conditions of temperature 23°C and humidity 90% RH. The measurement was performed twice for each of two test pieces, and the average of the four measured values was calculated as the oxygen transmission rate.
[0089] (8) Analysis by FT-IR-ATR method (P1 / P2) A 30 mm x 30 mm sample of the laminate was used to measure the spectrum using a Fourier transform infrared spectrophotometer FT / IR-6100 manufactured by JASCO Corporation, and the specified peaks P1 and P2 were detected using the peak detection mode of the analysis software. P1 / P2 was calculated from the obtained values of P1 and P2.
[0090] P1 / P2 was calculated at three different positions, and the values at the three points were averaged to determine P1 / P2 for that sample. Light source: High brightness ceramic light source Detector: TGS Beam splitter: Ge / KBr Measurement mode: ATR method (Ge prism, incident angle 45°) Measurement wave number range: 4,000 cm -1 ~600cm -1 ·Resolution: 4cm -1 Number of times: 32 Analysis: Peaks were detected using Spectra Manager Version 2 spectrum analysis program.
[0091] (9) The ratio m / s of the peak intensity m of the fragment ion derived from the metal element M to the peak intensity s of the fragment ion derived from the segment having a Si-O bond Using a time-of-flight secondary ion mass spectrometer TOF-SIMS5 manufactured by ION TOF and measurement software SURFACE LAB 7.1 manufactured by the same company, the peak intensity m of the fragment ion derived from the metal element M and the peak intensity s of the fragment ion derived from the segment having a Si-O bond were measured by secondary ion mass spectrometry for the center part of the coating layer, and the peak intensity ratio m / s was calculated. The measurement conditions are as follows.
[0092] Primary ion species: Bi + (2pA, 50μs) Acceleration voltage: 25kV Detected ion polarity: positive Measurement range: 100μm×100μm ·Resolution: :128×128 Etching ion species: O 2+ (2keV, 170nA) Etching area: 300μm×300μm Etching rate: 1sec / cycle.
[0093] (10) Peel strength On each of the laminates obtained in Examples 1 to 42 and Comparative Examples 1 to 9, a solid print layer was formed using the following ink A and ink B.
[0094] [Ink A: Richcure WL EB Cyan (Naigai Ink Mfg. Co., Ltd., electron beam curable waterless offset ink), contains photosensitive resin. Acrylic equivalent 166g / eq].
[0095] The electron beam curable ink A was transferred to various laminates. The ink was applied using an RI tester. The ink was then cured by irradiating the ink with an electron beam at an acceleration voltage of 110 kV and an exposure dose of 30 kGy using an electron beam irradiation device (EC250 / 30 / 90LS manufactured by Iwasaki Electric Co., Ltd.) to obtain a solid print.
[0096] [Ink B: "Rio Alpha (registered trademark)" S R39 indigo (manufactured by Toyo Ink Co., Ltd., solvent gravure ink for reverse printing), containing polyurethane resin].
[0097] Solvent ink B was transferred onto the various laminates. A bar coater No. 8 was used for the transfer method. Then, the ink was dried in an oven at 80°C for 1 minute to obtain a solid print.
[0098] Next, a mixed laminating adhesive (Takelac® A626 / Takenate® A50, manufactured by Mitsui Chemicals, Inc.) was applied to each solid print in a coating amount of 3.0 g / m. 2 The laminate was coated so that the thickness was 70 μm, and then laminated with a 70 μm thick non-oriented polypropylene film (CPP) (ZK-207, manufactured by Toray Film Processing Co., Ltd.). The laminate was then aged at 40°C for 3 days to obtain a laminate sample. The obtained laminate sample was cut into a 15 mm wide strip and a peel test was carried out using a Tensilon universal testing machine (RTG-1210, manufactured by Orientec Co., Ltd.) to measure the peel strength (unit: N / 15 mm) when peeled at 90° at 300 mm / min. Each measurement was carried out twice, and the average value was calculated to evaluate the adhesion.
[0099] When the peel strength was less than 2.0 N / 15 mm, the adhesion was judged to be insufficient, when it was 2.0 N / 15 mm or more and less than 3.0 N / 15 mm, the adhesion was judged to be good, when it was 3.0 N / 15 mm or more and less than 4.0 N / 15 mm, the adhesion was judged to be better, and when it was 4.0 N / 15 mm or more, the adhesion was judged to be extremely good.
[0100] [Example 1] (Formation of metal layer or inorganic compound layer) An aluminum oxide layer of 12 nm was formed as an inorganic compound layer on one side of a 12 μm-thick biaxially oriented polyethylene terephthalate film (Lumirror (registered trademark) P60 manufactured by Toray Industries, Inc.) The aluminum oxide layer was deposited by a reactive deposition method in which aluminum is evaporated and then oxidized by introducing oxygen into the deposition area.
[0101] (Formation of coating layer) As a water-soluble polymer, polyvinyl alcohol (hereinafter sometimes abbreviated as PVA, Poval 28-98 manufactured by Kuraray Co., Ltd.) was added to a solvent of water / isopropyl alcohol = 97 / 3 by mass ratio, and heated and stirred at 90 ° C to obtain a water-soluble polymer solution with a solid content of 10 mass %. Next, a solution of 6.7 g of TEOS and 2.7 g of methanol was mixed and stirred while adding 10.6 g of 0.02 N hydrochloric acid solution dropwise to obtain a TEOS hydrolyzed solution. Furthermore, a solution of 6.1 g of 3-acryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.: KBM-5103) and 10.6 g of methanol was mixed and stirred while adding 2.4 g of 0.1 N hydrochloric acid solution dropwise to obtain a (meth)acryloyl group-containing hydrolyzed solution.
[0102] The water-soluble polymer solution was mixed with the TEOS hydrolyzed solution so that the ratio of the PVA solid content of the water-soluble polymer solution to the SiO2 equivalent mass of TEOS was PVA solid content / SiO2 equivalent mass=35 / 65. The (meth)acryloyl group-containing hydrolyzed solution was added to the resulting mixture so that the (meth)acryloyl group content was 1.12 mol% relative to the total molar amount of metal elements contained in the coating layer, and the mixture was diluted with water so that the total solid content was 13 mass% to obtain a coating solution. The coating solution was applied onto the above-mentioned aluminum oxide layer and dried at 150°C for 1 minute to obtain a laminate.
[0103] [Example 2] A laminate was obtained in the same manner as in Example 1, except that the coating layer was dried and then further heat-treated at 80° C. for one week.
[0104] [Example 3] A laminate was obtained in the same manner as in Example 2, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 0.17 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0105] [Example 4] A laminate was obtained in the same manner as in Example 2, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 0.28 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0106] [Example 5] A laminate was obtained in the same manner as in Example 2, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 0.34 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0107] [Example 6] A laminate was obtained in the same manner as in Example 2, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 0.56 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0108] [Example 7] A laminate was obtained in the same manner as in Example 2, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 0.79 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0109] [Example 8] A laminate was obtained in the same manner as in Example 2, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 1.01 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0110] [Example 9] A laminate was obtained in the same manner as in Example 2, except that the water-soluble polymer in the coating layer was modified polyvinyl alcohol ("Exceval (registered trademark)" RS-1717, manufactured by Kuraray Co., Ltd.) and the (meth)acryloyl group-containing hydrolyzed liquid was added so that the (meth)acryloyl group was 1.01 mol % relative to the total molar amount of metal elements contained in the coating layer. [Example 10] A laminate was obtained in the same manner as in Example 9, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 1.12 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0111] [Example 11] A laminate was obtained in the same manner as in Example 2, except that the water-soluble polymer of the coating layer was modified polyvinyl alcohol (ZF-15 manufactured by Japan Vinyl Acetate & Poval Co., Ltd.) and the (meth)acryloyl group-containing hydrolyzed liquid was added so that the (meth)acryloyl group was 1.01 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0112] [Example 12] A laminate was obtained in the same manner as in Example 2, except that the water-soluble polymer in the coating layer was modified polyvinyl alcohol ("Exceval (registered trademark)" HR-3010, manufactured by Kuraray Co., Ltd.) and the (meth)acryloyl group-containing hydrolyzed liquid was added so that the (meth)acryloyl group was 1.01 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0113] [Example 13] A laminate was obtained in the same manner as in Example 2, except that the water-soluble polymer of the coating layer was modified polyvinyl alcohol (DF-20 manufactured by Japan Vinyl Acetate & Poval Co., Ltd.) and the (meth)acryloyl group-containing hydrolyzed liquid was added so that the (meth)acryloyl group was 1.01 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0114] [Example 14] A laminate was obtained in the same manner as in Example 2, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 1.68 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0115] [Example 15] A laminate was obtained in the same manner as in Example 2, except that the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer was added so that the (meth)acryloyl group was 5.59 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0116] [Example 16] (Formation of metal layer or inorganic compound layer) An aluminum oxide layer of 12 nm was formed as an inorganic compound layer on one side of a 12 μm-thick biaxially oriented polyethylene terephthalate film (Lumirror (registered trademark) P60 manufactured by Toray Industries, Inc.) The aluminum oxide layer was deposited by a reactive deposition method in which aluminum is evaporated and then oxidized by introducing oxygen into the deposition area. (Formation of coating layer) As a water-soluble polymer, polyvinyl alcohol (Poval 28-98 manufactured by Kuraray Co., Ltd.) was added to a solvent of water / isopropyl alcohol = 97 / 3 by mass ratio, and heated and stirred at 90 ° C to obtain a water-soluble polymer solution with a solid content of 10 mass %. Next, a solution of 6.4 g of TEOS, 0.3 g of 3-acryloxypropyltrimethoxysilane (KBM-5103 manufactured by Shin-Etsu Chemical Co., Ltd.), and 2.7 g of methanol was mixed and stirred while adding dropwise 10.6 g of 0.02 N hydrochloric acid solution to obtain a (meth)acryloyl group-containing TEOS hydrolyzate solution.
[0117] The water-soluble polymer solution was mixed with the (meth)acryloyl group-containing TEOS hydrolyzate solution so that the ratio of the PVA solid content of the water-soluble polymer solution to the SiO2-equivalent mass of TEOS was PVA solid content / SiO2-equivalent mass = 35 / 65. The mixture was diluted with water to a total solid content of 13 mass% to obtain a coating solution. The coating solution was applied onto the above-mentioned aluminum oxide layer, dried at 150°C for 1 minute, and then heat-treated at 80°C for 1 week to obtain a laminate.
[0118] [Example 17] A laminate was obtained in the same manner as in Example 7, except that in preparing the coating solution for the coating layer, the ratio of the PVA solid content of the water-soluble polymer solution to the SiO2 equivalent mass of the TEOS hydrolyzed solution was PVA solid content / SiO2 equivalent mass = 20 / 80.
[0119] [Example 18] A laminate was obtained in the same manner as in Example 4, except that in preparing the coating solution for the coating layer, the ratio of the PVA solid content of the water-soluble polymer solution to the SiO2 equivalent mass of the TEOS hydrolyzed solution was PVA solid content / SiO2 equivalent mass = 80 / 20.
[0120] [Example 19] A laminate was obtained in the same manner as in Example 6, except that in preparing the coating solution for the coating layer, the ratio of the PVA solid content of the water-soluble polymer solution to the SiO2 equivalent mass of the TEOS hydrolyzed solution was PVA solid content / SiO2 equivalent mass = 55 / 45.
[0121] [Example 20] A laminate was obtained in the same manner as in Example 2, except that in preparing the coating solution for the coating layer, the ratio of the PVA solid content of the water-soluble polymer solution to the SiO2 equivalent mass of the TEOS hydrolyzed solution was PVA solid content / SiO2 equivalent mass = 5 / 95.
[0122] [Examples 21 to 23] A laminate was obtained in the same manner as in Example 8, except that the coating thickness of the coating layer was changed.
[0123] [Example 24] A laminate was obtained in the same manner as in Example 6, except that in the preparation of the coating liquid for the coating layer, zirconium chelate ("Orgatix (registered trademark)" ZC-300: zirconium lactate ammonium salt, solid content concentration 12 mass %, manufactured by Matsumoto Fine Chemical Co., Ltd., was further added in an amount of 2.98 mol % relative to the total molar amount of metal elements contained in the coating layer (excluding the (meth)acryloyl group-containing hydrolyzed liquid of the coating layer), and the coating liquid was applied onto the aluminum oxide layer, dried at 120°C for 1 minute, and then heat-treated at 80°C for 1 week.
[0124] [Example 25] A laminate was obtained in the same manner as in Example 24, except that a biaxially oriented polypropylene film having a thickness of 12 μm (polypropylene film manufactured by Toray Industries, Inc., melting point 170° C., Sa 21 nm) was used in forming the metal layer or inorganic compound layer.
[0125] [Example 26] A laminate was obtained in the same manner as in Example 24, except that a 12 μm-thick biaxially oriented polypropylene film (polypropylene film manufactured by Toray Industries, Inc., melting point 170° C., Sa 21 nm) was used in forming the metal layer or inorganic compound layer, and that a titanium chelate (TC-310: titanium lactate manufactured by Matsumoto Fine Chemical Co., Ltd., solid content concentration 44 mass%) was added instead of a zirconium chelate in the preparation of the coating liquid for the coating layer, at 0.61 mol% relative to the total molar amount of the metal elements contained in the coating layer (excluding the (meth)acryloyl group-containing hydrolyzate liquid of the coating layer).
[0126] [Examples 27 to 35] Laminates were obtained in the same manner as in Example 26, except that in preparing the coating solution for the coating layer, the (meth)acryloyl group-containing hydrolyzed liquid was added in an amount of 0.17 mol%, 0.28 mol%, 0.34 mol%, 0.56 mol%, 0.79 mol%, 1.01 mol%, 1.12 mol%, 1.68 mol%, or 5.59 mol% based on the total molar amount of the metal elements contained in the coating layer, and further, titanium chelate (TC-310 manufactured by Matsumoto Fine Chemical Co., Ltd.: titanium lactate, solid content concentration 44 mass%) was added in an amount of 1.81 mol% based on the total molar amount of the metal elements contained in the coating layer (excluding the (meth)acryloyl group-containing hydrolyzed liquid for the coating layer).
[0127] [Example 36] A laminate was obtained in the same manner as in Example 26, except that in preparing the coating solution for the coating layer, titanium chelate (TC-310: titanium lactate manufactured by Matsumoto Fine Chemical Co., Ltd., solid content concentration 44 mass%) was added in an amount of 3.56 mol% relative to the total molar amount of metal elements contained in the coating layer (excluding the (meth)acryloyl group-containing hydrolyzed solution of the coating layer).
[0128] [Example 37] A laminate was obtained in the same manner as in Example 26, except that in preparing the coating solution for the coating layer, titanium chelate (TC-400: titanium triethanolamine manufactured by Matsumoto Fine Chemical Co., Ltd., solid content concentration 79 mass%) was added in an amount of 8.15 mol% relative to the total molar amount of metal elements contained in the coating layer (excluding the (meth)acryloyl group-containing hydrolyzed solution of the coating layer).
[0129] [Examples 38 to 41] Laminates were obtained in the same manner as in Example 26, except that in preparing the coating solution for the coating layer, zirconium chelate (Orgatix ZC-300 manufactured by Matsumoto Fine Chemical Co., Ltd.: zirconium lactate ammonium salt, solids concentration 12 mass%) was added at 0.20 mol%, 0.41 mol%, 17.7 mol%, and 19.7 mol% relative to the total molar amount of metal elements contained in the coating layer (excluding the (meth)acryloyl group-containing hydrolyzed solution of the coating layer).
[0130] [Example 42] A laminate was obtained in the same manner as in Example 25, except that an undercoat layer was formed on one side of the biaxially oriented polypropylene film and then an inorganic compound layer was formed.
[0131] The undercoat layer was formed by the following procedure. To 100 parts by mass of "Hydran (registered trademark)" AP-201 (manufactured by DIC Corporation, solid content concentration 23%), which is a polyester urethane-based water-dispersible resin, 6 parts by mass of the melamine compound "Amidea (registered trademark)" APM (manufactured by DIC Corporation) was added as a crosslinking agent, and 1 part by mass of "Catalyst" PTS (manufactured by DIC Corporation), which is a water-soluble acidic compound, was added as a crosslinking catalyst. Pure water was then added to adjust the total solid content concentration to 10%, to obtain a mixed coating agent. This mixed coating liquid was applied to one side of a biaxially oriented polypropylene film and dried at 110°C for 30 seconds to form an undercoat layer with a thickness of 700 nm.
[0132] [Comparative Example 1] A laminate was obtained in the same manner as in Example 1, except that no coating layer was formed.
[0133] [Comparative Example 2] A laminate was obtained in the same manner as in Example 3, except that the (meth)acryloyl group-containing hydrolyzed liquid was not added.
[0134] [Comparative Example 3] A laminate was obtained in the same manner as in Example 3, except that the amount of the (meth)acryloyl group-containing hydrolyzed liquid added was such that the (meth)acryloyl group was 18.72 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0135] [Comparative Example 4] A laminate was obtained in the same manner as in Example 3, except that an isocyanate group-containing hydrolyzed liquid (3-isocyanatepropyltriethoxysilane (X-12-1308ES, with isocyanate protecting group, manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of 3-acryloxypropyltrimethoxysilane (KBM-5103, manufactured by Shin-Etsu Chemical Co., Ltd.) in the (meth)acryloyl group-containing hydrolyzed liquid in Example 1) was added in place of the (meth)acryloyl group-containing hydrolyzed liquid, so that the isocyanate group accounted for 1.12 mol% relative to the total molar amount of metal elements contained in the coating layer.
[0136] [Comparative Example 5] A laminate was obtained in the same manner as in Example 3, except that a vinyl group-containing hydrolyzed liquid (a (meth)acryloyl group-containing hydrolyzed liquid in Example 1 using vinyltriethoxysilane (Shin-Etsu Chemical Co., Ltd.: KBE-1003) instead of 3-acryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.: KBM-5103) in the (meth)acryloyl group-containing hydrolyzed liquid in Example 1) was added in place of the (meth)acryloyl group-containing hydrolyzed liquid, such that the vinyl group accounted for 1.12 mol % relative to the total molar amount of metal elements contained in the coating layer.
[0137] [Comparative Example 6] A laminate was obtained in the same manner as in Example 2, except that a biaxially oriented polypropylene film was used as the base film and the (meth)acryloyl group-containing hydrolyzed liquid was not added.
[0138] [Comparative Example 7] A laminate was obtained in the same manner as in Example 3, except that a biaxially oriented polypropylene film was used as the base film, no (meth)acryloyl group-containing hydrolysis liquid was added, and the coating liquid was applied and then dried at 160°C for 1 minute.
[0139] [Comparative Example 8] A laminate was obtained in the same manner as in Example 3, except that an epoxy group-containing hydrolyzed liquid (3-glycidoxypropyltriethoxysilane (KBE-403 manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of 3-acryloxypropyltrimethoxysilane (KBM-5103 manufactured by Shin-Etsu Chemical Co., Ltd.) in the (meth)acryloyl group-containing hydrolyzed liquid in Example 1) was added in place of the (meth)acryloyl group-containing hydrolyzed liquid, so that the epoxy group was 1.12 mol% relative to the total molar amount of metal elements contained in the coating layer.
[0140] [Comparative Example 9] A laminate was obtained in the same manner as in Example 3, except that a carboxyl group-containing hydrolyzed liquid (X-12-1135, manufactured by Shin-Etsu Chemical Co., Ltd., an aqueous silane coupling agent having a carboxyl group in the organic functional group, hydrolyzed) was added instead of the (meth)acryloyl group-containing hydrolyzed liquid so that the carboxyl group was 1.12 mol% relative to the total molar amount of the metal elements contained in the coating layer.
[0141] [Comparative Example 10] (Formation of metal layer or inorganic compound layer) An aluminum oxide layer of 12 nm was formed as an inorganic compound layer on one side of a 12 μm-thick biaxially oriented polyethylene terephthalate film (Lumirror (registered trademark) P60 manufactured by Toray Industries, Inc.) The aluminum oxide layer was deposited by a reactive deposition method in which aluminum is evaporated and then oxidized by introducing oxygen into the deposition area.
[0142] (Formation of coating layer) As a water-soluble polymer, polyvinyl alcohol (hereinafter sometimes abbreviated as PVA, Poval 28-98 manufactured by Kuraray Co., Ltd.) was added to a solvent of water / isopropyl alcohol = 97 / 3 by mass ratio, and heated and stirred at 90 ° C to obtain a water-soluble polymer solution with a solid content of 10 mass %. Next, the water-soluble polymer solution PVA, 3-acryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.: KBM-5103), and titanium chelate (manufactured by Matsumoto Fine Chemical Co., Ltd. TC-310: titanium lactate, solid content concentration 44 mass %) were mixed so that the solid content ratio was 4 / 5 / 1, and diluted with water to a total solid content of 13 mass % to obtain a coating liquid. The coating liquid was applied onto the above-mentioned aluminum oxide layer and dried at 120 ° C for 2 minutes to obtain a laminate.
[0143] [Table 1]
[0144] [Table 2]
[0145] [Table 3]
[0146] [Table 4]
[0147] [Table 5]
[0148] [Table 6]
[0149] In Comparative Example 2, the barrier property was good, but since the coating layer did not contain a (meth)acryloyl group, adhesion to the printed layer using electron beam curable ink was not obtained.
[0150] In Comparative Example 3, since the coating layer contains many (meth)acryloyl groups, adhesion to a printed layer using an electron beam curable ink is good; however, adhesion to a gravure ink containing a urethane resin is significantly deteriorated due to a decrease in hydroxyl groups. Furthermore, it is believed that the acryloyl groups, which are highly hydrophobic and have a large molecular weight, increase the voids in the coating layer, thereby worsening the barrier properties.
[0151] In Comparative Examples 4 and 5, isocyanate groups and vinyl groups were used instead of (meth)acryloyl groups, and although the barrier properties were good, adhesion to the printed layer using electron beam curable ink was not obtained. It is believed that the isocyanate groups reacted with other components in the coating layer and were deactivated. Vinyl groups have a small molecular weight and are advantageous in terms of barrier properties, but compared with (meth)acryloyl groups, they generate less radicals and are therefore thought to have failed to provide sufficient adhesion.
[0152] In Comparative Example 7, the drying temperature for the coating layer was high, and the coating layer was damaged by shrinkage of the film, causing minute cracks, which is thought to have significantly deteriorated the oxygen barrier properties in particular.
[0153] In Comparative Examples 8 and 9, epoxy and carboxyl groups were used instead of (meth)acryloyl groups, and although the barrier properties were good, adhesion to the printed layer using electron beam curable ink was not obtained. It is considered that the amount of radical generation was small compared to (meth)acryloyl groups, and sufficient adhesion was not obtained. In addition, the highly hydrophobic (meth)acryloyl group is likely to be unevenly distributed on the surface of the coating layer, so adhesion can be improved with a small amount, but hydrophilic functional groups are likely to diffuse into the coating layer, and it is considered that it is difficult to improve adhesion with a small amount.
[0154] From the above results, the present invention can provide a laminate having good adhesion to a printed layer using various inks and good barrier properties. Furthermore, even in a laminate using a polyolefin resin substrate with low heat resistance, a laminate having good adhesion to a printed layer using various inks and good barrier properties can be provided. [Explanation of symbols]
[0155] 1. Base film 2 Metal layer and / or inorganic oxide layer 3 Covering layer
Claims
1. A laminate in which a metal layer and / or an inorganic compound layer, and a coating layer are laminated in this order on at least one surface of a base film, wherein the ratio X / Y of the emission intensity X of an emission peak to the emission intensity Y of a reference peak measured under the following measurement conditions from the coating layer side is 5 or more and 300 or less. <Measurement conditions> The coated layer side of the laminate is 1×10 -4 After contacting the laminate with a 1.0 mol / L solution of 4-Nitro-7-piperazino-2,1,3-benzoxadiazole in tetrahydrofuran (THF) at 60°C for 30 minutes, the laminate was immersed and washed twice in THF, and then cut into a 15 mm x 15 mm piece. In the emission spectrum measurement, the laminate was excited at 470 nm, and the peak intensity of the emission maximum observed at 520 to 550 nm was calculated. <Base Peak> 1x10 -5 A THF solution of 4-Nitro-7-piperazino-2,1,3-benzoxadiazole (mol / L) was measured in a quartz glass cell with an optical path length of 10 mm in the same manner as for the laminate.
2. 2. The laminate according to claim 1, wherein the coating layer comprises a hydrolysate of a water-soluble resin and a metal alkoxide and / or a polycondensate thereof.
3. The laminate according to claim 1 or 2, wherein the coating layer has a thickness of 200 nm or more and 600 nm or less.
4. The laminate according to claim 1 or 2, wherein the metal layer and / or the inorganic compound layer contains aluminum.
5. The laminate has a water vapor permeability of 1.0 g / m 2 / day or less, and the oxygen permeability is 1.0 cc / m 2 The laminate according to claim 1 or 2, wherein the average molecular weight is 1000 or less.
6. The laminate according to claim 2 , wherein the coating layer contains 0.25 mol % or more and 1.25 mol % or less of (meth)acryloyl groups relative to the total molar amount of metal elements contained in the coating layer.
7. 3. The laminate according to claim 1, wherein the ratio X / Y of the emission intensity X of an emission peak to the emission intensity Y of a reference peak measured under the following measurement conditions from the coating layer side of the laminate is 18 or more and 100 or less. <Measurement conditions> The coated layer side of the laminate is 1×10 -4 After contacting the laminate with a THF solution of 1.2 mol / L of 4-Nitro-7-piperazino-2,1,3-benzoxadiazole at 60°C for 30 minutes, the laminate was immersed and washed twice in THF, and then cut into a 15 mm x 15 mm piece. In the emission spectrum measurement, the laminate was excited at 470 nm, and the peak intensity of the emission maximum observed at 520 to 550 nm was calculated. <Base Peak> 1x10 -5 A THF solution of 4-Nitro-7-piperazino-2,1,3-benzoxadiazole (mol / L) was measured in a quartz glass cell with an optical path length of 10 mm in the same manner as for the laminate.
8. 3. The laminate according to claim 1, wherein the substrate film is a polyolefin-based resin film.
9. The laminate according to claim 1 or 2, wherein the ratio P1 / P2 of the following peak intensities P1 and P2 detected by measuring the coating layer by an FT-IR-ATR method (total reflection Fourier transform infrared spectroscopy) is 3.5 or more and 8.0 or less. P1: 1,050-1,080cm -1 Intensity of the largest peak present in P2: 920-970cm -1 Intensity of the largest peak present in
10. 3. The laminate according to claim 1 or 2, wherein the coating layer contains a metal element M in addition to a water-soluble resin and a hydrolysate of a metal alkoxide and / or a polycondensate thereof, and a ratio m / s of a peak intensity m of a fragment ion derived from the metal element M to a peak intensity s of a fragment ion derived from a segment having a Si—O bond, as measured by a time-of-flight secondary ion mass spectrometer (TOF-SIMS), is 0.05 or more and 10.00 or less. <Measurement conditions> Primary ion species: Bi + (2 pA, 50 μs) Acceleration voltage: 25 kV Detected ion polarity: positive Measurement range: 100 μm x 100 μm Resolution: 128×128 Etching ion species: O 2+ (2keV, 170nA) Etching area: 300 μm × 300 μm Etching rate: 1 sec / cycle
11. The laminate according to claim 1 or 2, wherein the base film is a film derived from recycling.
12. The laminate according to claim 1 or 2, which is used for packaging material applications.
13. The laminate according to claim 1 or 2, which is used for printing with electron beam curable ink.
Citation Information
Patent Citations
Laminate and package using the same
JP2022020129A
Electron beam-curable water-based flexo ink for surface printing and boilable retort pouch using same
WO2019069736A1
Charged particle beam device
WO2020183596A1